Conversando com Mães e Professoras sobre as Orquídeas e os Girassóis da Exclusão: teorias subjetivas sobre práticas de educação e desenvolvimento infantil, em instituições comunitárias - Gomes, Rita de Cássia Oliveira (2004)
Ahead of the doubts that involve the subjective theories and as if articulate in the education and children cares, if it composed the object of inquiry of this research. Its main objective was to give visibility to the beliefs and values of mothers and teachers, of four institutions of communitarian Childhood Education, in the city of Duque de Caxias. The instruments used for the production of data had been: Data of the Unit of Infantile Education, Personal datas (of the mothers and, of all the teachers of the institutions), Interview, Hierarchy of the five selected objectives and Questionnaire of Educational Objectives (applied the 12 mothers and 08 teachers). The analysis evidences some of the beliefs and values of mothers and teachers on: objectives in the education of the children; educational objectives; strategies on forms to educate; conceptions of children autonomous, sensible, "ideal", "easy" and "difficult"; evaluation of the efficiency of itself exactly and the other in the education of the child; the race, gender, class differences; and the definitions of mothers and teachers, for the educational objectives. In this movement of analysis and deepening it is standed out: the insufficient vacant number to the Childhood Education in the city of Duque de Caxias; the right to the Childhood Education; the little access of the population to the information and the laws; the absence/urgency of public politics; the racial relations and of gender as important aspects of the Childhood Education; the boardings quantitative and qualitative in the research; the relevancy of the number of participants and the instruments; the alterations and limitations of the same ones; suggestions of revalidation of instruments; the inclusion and deepening of educational objective studies involving and formation of teachers. The analyses and understandings developed in this thesis add information to the transcultural study developed by the Brazil-Germany Project and contribute for the construction of an integrated system of quality of the Childhood Education, when investing in the educational research and the professional formation.